A case study on stress experienced by teachers in an urban secondary school in Sarawak - Yong, Choo Tiong. (1998)
This case study examined the stress experienced by teachers in a selected urban secondary school in Sibu Division, Saralvak. The five main objectives of the study was (i) to identify the main stress factors, (ii) to identify the main stressors, (iii) to determine the levels of teacher stress, (iv) to examine the relationship between teachers' stress levels and students' school examination performance, (v) to identify the different responses to stress due to demogaphicat differences of the teachers. A survey questionnaire was used for this study. The questionnaire was modtied from the Occupational Stress Inventory for Teachers in Malaysia. To triangulate the findings, participant observations, document study and interviews were also employed. The researcher spent 6 weeks doing the participant observation and interviews. He taught in some classes and took part in school activities. From a total of 105 teachers in the school, 86 responded to the questionnaire. Forty-five teachers were further interviewed. The findings showed that the best predictors for stress factors were the workload and student factors. The most prevailing stressors were 'poor atbtude of students toxvards learning', 'having to deal with students who continually misbehave', 'having to deal with weak or incompetent students', 'high expectation from school principal', 'having to teach large classes', 'classroom is too congested' and 'students do not respect teachers'. None of the teachers were free from stress. 30.69/0 of the respondents were mildly stressed, 44.790 were moderately stressed, 18.8% very stressful and 5.9% were extremely stressful. The students' performance according to subjects revealed that better performance were enhanced when teachers were at moderate stress or much stress levels. When teachers were experiencing mild stress or extreme stress, the students' performance was relatively low. The iinlngs in this study showed that there was no differewes in the teachers' stress level due to the different demographical differences. Hence, in this school, teachers' stress levels were not affected by their gender, places of ori.gin, races, qualifications, length in service, age, different number of teaching periods, subjects, level of students and classes taught.